Turning to Online Forums for Legal Information: A Case Study of GDPR’s Legitimate Interests - Kyi, Lin; Santos, Cristiana; Ammanaghatta Shivakumar, Sushil; Roesner, Franziska; Biega, Asia (Lecture Notes in Computer Science)

Why Engineering Students Choose a Career in Teacher Education – Qualitative Analysis of Bachelor Students' Motives - Vernholz, Mats; Temmen, Katrin (Towards inclusive and egalitarian vocational education and training: Key challenges and strategies from a holistic and multi-contextual approach. Proceedings of the 6th Crossing Boundaries Conference in Vocational Education and Training)

Section 39 (Digital Markets Act) - Bartlitz, David; Gräfe, Alexander (Handbuch des EU-Wirtschaftsrechts)

Diskussionsbeitrag zu Klimaquote, Klimagovernance und Rechtsformzusatz "klimaneutral" - Bartlitz, David (Verhandlungen des 74. Deutschen Juristentages Stuttgart 2024)

Reformation mit Hanns Dieter Hüsch feiern 31. Oktober 2025

How does practice modulate fake-production costs in a basketball task? Analyses of frequency distributions and mixture effects - Böer, Nils Tobias; Schütz, Christoph; Weigelt, Matthias; Güldenpenning, Iris (Psychological Research)
Abstract The execution of incompatible actions imposes costs on action planning, commonly known as response-response incompatibility-costs. This phenomenon is also evident in sports: A basketball player who performs a pass in one direction whilst orienting the head into the contrary direction (pass with head fake) needs more time to initiate the action as if pass direction and head orientation are the same (pass without head fake). The aim of this study was twofold: First, we present a re-analysis of the data from Böer et al. (Psychological Research 88:523–524, 2024) using mixture effect modelling (Miller, Behavior Research Methods 38:92–106, 2006) explore if fake-production costs manifest continuously (uniform effect) in all participants or if some participants show fake-production costs occasionally but substantially (mixed effect). Second, we collected data of a control group which was analysed with the previous data of the practice group and fitted initiation times (ITs) to an ex-Gaussian distribution. The analysis of mixture effects revealed that most participants exhibited a uniform effect when they didn’t have time to mentally prepare the movement. This pattern was not changed by practice, suggesting fake-production costs can’t be overcome by practice alone without mental preparation time. The analysis of mean ITs revealed improvements in the practice group but not in the control group, independent of the type of pass performed. The distribution analyses complemented these findings as it showed that the improvement in participants’ performance with increasing practice can mainly be attributed to a reduction of the exponential part of the distribution (parameter tau).
Keywords: Sport Psychology; Sport Science; Deception; Distribution Analysis

The mere presence of a social partner modulates fake-production costs - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (57th Herbsttreffen der experimentellen Kognitionspsychologie (HExKoP))
Keywords: Deception; Sport Psychology; Social Interaction

Erfolgreich Studieren – sinnvolle Lernstrategien erlernen - Nölle, Florian; Schmid, Hans-Joachim (Tag der Lehre 2025)

Overcoming disciplinary cultures as innovation barriers: realising transfer potentials - Sloane, Hannah Sabrina

Listening to students' voices: Engaged pedagogy as a pathway to pedagogical possibilities. - Lin-Januszewski, Liang-Wen (Sociology)
This study explores undergraduate sociology students’ perceptions of conventional pedagogical practices and their aspirations for an ideal learning environment at a regional German university. Drawing on semi-structured interviews with 41 students enrolled between 2021 and 2023, the research investigates how students envision the study of sociology and their preferences for pedagogical approaches. The findings reveal that students’ diverse visions converge on common themes aligning with engaged pedagogy and critical pedagogy principles. Students express a desire for learning environments that challenge existing forms of domination, promote active knowledge acquisition, and foster mutual respect. They seek meaningful knowledge that connects theory to practice, facilitates personal growth, and empowers them to effect social change. The study contributes to ongoing debates about pedagogical practices in higher education, especially in sociology, by providing empirical evidence of students’ subjective experiences and desires, emphasising the need for engaged pedagogy that nurtures holistic development and values students’ agency.
Keywords: bell hooks; critical pedagogy; engaged pedagogy; pedagogy of sociology; student voices

NL2LS: LLM-based Automatic Linking of Knowledge Graphs - Ihtassine, Reda; Firmansyah, Asep Fajar; Srivastava, Nikit; Ali, Manzoor; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed (Proceedings of the 12th Knowledge Capture Conference 2025, K-CAP 2025, The Thirteenth International Conference on Knowledge Capture, December 10 - 12, 2025, Dayton, Ohio, USA)
Keywords: Srivastava ali dice enexa firmansyah ihtassine ngonga sailproject sherif whale

Promoting women researchers in STEM: The case of German higher education. - Chang, Chen-Wei; Lin-Januszewski, Liang-Wen (Towards a gender-inclusive future: National strategies for cultivating women researchers in STEM)

Fostering Authenticity and Disciplinary Dialogue in the Age of AI - Schmöckel, Sabrina; Sloane, Hannah Sabrina

How to Conduct Participatory Creative Visual Methods With Young Adults - Lin-Januszewski, Liang-Wen

„Ein Komponistenleben des 20. Jahrhunderts“. Erste Bestandsaufnahme und Forschungsfragen zu Hans Werner Henzes Privatbibliothek als Sondersammlung - Tumat, Antje (Musik, Netzwerke, Selbstzeugnisse. Aktuelle Forschung zu Hans Werner Henze)
Henzes Privatbibliothek aus seinem Besitz in La Leprara bei Marino südlich von Rom, in dem er fast fünfzig Jahre seines Lebens verbracht und viele seiner großen Werke geschrieben hat, wurde nach dem Verkauf des Anwesens der Bibliothek des Musikwissenschaftlichen Seminars der Universität Paderborn/Hochschule für Musik Detmold per Schenkung als Sondersammlung übergeben. Die Privatbibliothek ist nunmehr vollständig inventarisiert und somit der Öffentlichkeit zugänglich gemacht. Der Text beschreibt in einer ersten Bestandsaufnahme den Charakter und die Schwerpunkte dieser Sammlung und stellt erste Forschungsfragen an den Bestand: Er fragt etwa nach den Erkenntnissen, die sich aus den über 600 handschriftlichen Widmungen in Büchern und über 150 Widmungen in Noten im Hinblick auf Henzes persönliches Netzwerk und seine Biografie ergeben und wertet einige Widmungskonvolute aus. Abstract (EN) Henze's personal library, which belonged to him in La Leprara near Marino south of Rome, where he spent almost fifty years of his life and wrote many of his important works, was donated to the library of the Musicology Seminar of the University of Paderborn/Detmold University of Music as a collection after the sale of the estate. The private library has now been completely catalogued and is thus accessible to the public. The text provides an initial overview of the character and focus of this collection and poses research questions about the holdings: For example, it asks what insights can be gained from the more than 600 handwritten dedications in books and over 150 dedications in sheet music with regard to Henze's personal network and his biography, and evaluates some of the collections of dedications.
Keywords: Hans Werner Henze; Privatbibliothek; Neue Musik

Musik, Netzwerke, Selbstzeugnisse. Aktuelle Forschung zu Hans Werner Henze
Der Sammelband veröffentlicht die Beiträge des internationalen Symposiums zu Hans Werner Henze, das im Dezember 2022 in Detmold stattfand und aktuelle Beiträge zur Henze-Forschung mit unterschiedlichsten inhaltlichen Schwerpunkten wie Filmmusik, Gender Studies oder Musikanalyse versammelt. Nach zwei Aufsätzen zu neuen Henze-Briefausgaben (Irmlind Capelle / Elena Minetti / Dennis Ried / Antje Tumat einerseits und Andreas Hérm Baumgartner / Wolfgang Rathert andererseits) und einem ersten Überblick über Henzes Privatbibliothek als Sondersammlung (Antje Tumat) diskutiert Adrian Kuhl Die Zusammenarbeit Tatjana Gsovskys und Hans Werner Henzes beim Ballett Der Idiot. Zafer Özgen beschäftigt sich anschließend mit Kompositionsstrategien in Henzes frühen Opern, Federica Marsico betrachtet die Figur des Orpheus bei Henze aus Gender-Perspektive und Benedikt Leßmann widmet sich Henzes Filmmusik. Den Abschluss bildet ein Roundtable mit Zeitzeugen, bei dem ehemalige Kolleginnen und Kollegen, Freunde und andere mit Henze verbundene Personen aus ihrer Zusammenarbeit mit Henze berichten. Teilnehmende waren Henzes langjähriger Freund und enger Mitarbeiter in Montepulciano Gastón Fournier-Facio (Rom) und der Regisseur, Geschäftsführer der Henze-Stiftung und letzte Lebensbegleiter Henzes Michael Kerstan (Nürnberg), Simon Obert von der Paul Sacher Stiftung (Basel), dem Aufbewahrungsort der Sammlung Hans Werner Henze, sowie Peter Petersen (Hamburg) als Stellvertreter der frühen musikwissenschaftlichen Henze-Forschung.

Zu Heidegger - Kommunikationsanalytische Studien - Markewitz, Friedrich
Martin Heideggers Einfluss reicht bis heute weit über enge disziplinäre Grenzen hinaus in die verschiedenen Geistes- und Kulturwissenschaften sowie die gesamtgesellschaftliche Öffentlichkeit hinein. Gleichzeitig werden er und seine Philosophie, insbesondere seit der Veröffentlichung seiner Denktagebücher, der ‚Schwarzen Hefte‘, aufgrund nationalsozialistischer Verstrickungen und antisemitischer Konnotationen kontrovers diskutiert. Trotz seiner diskursiven Herausgehobenheit und Relevanz stehen linguistische Aufarbeitungen zu Heideggers Kommunikationsverhalten bis heute weitestgehend aus. Die vorliegende kommunikationsanalytische Studie versteht sich als erster umfassender Versuch, Heideggers Kommunikationsverhalten in den Blick zu nehmen, um Charakteristika wie Problematiken des Heideggerischen Sprachgebrauchs aufzuarbeiten sowie zu reflektieren.
Keywords: Linguistische Hermeneutik; Kommunikationsanalyse; Invektivitätsforschung; Begriffsarbeit

Sprache im erkenntnistheoretischen Werk Ludwik Flecks – Reflexionen und Anschlüsse - Markewitz, Friedrich; Ptashnyk, Stefaniya (Aptum - Zeitschrift für Sprachkritik und Sprachkultur)
This article examines the role of language in Ludwik Fleck’s epistemological work. Two objectives are pursued: Firstly, Fleck’s statements on language scattered throughout his oeuvre are to be systematized and reflected upon. Secondly, the question is asked of which statements of linguists and philosophers from the 19th and 20th centuries can be related to Fleck's work. The basic idea is that Fleck's reflections on thought styles and thought collectives can also be applied to his work to identify possible influences and correlations between Fleck’s remarks on language and those of other philosophers and linguists. Analyzing Fleck's ideas on language and their connections to the theoretical and philosophical considerations of his predecessors reveals his relativistic and deterministic conception of language. According to this conception, language is a central influencing factor in perception and cognition, constitutively bound to its use in thought collectives.

Tarnschrift - Markewitz, Friedrich; Bäumer, Benjamin (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)

Diskreditieren - Markewitz, Friedrich (Diskursmonitor. Glossar zur strategischen Kommunikation in öffentlichen Diskursen)